Robust arterial transit time and cerebral blood flow estimation using combined acquisition of Hadamard‐encoded multi‐delay and long‐labeled long‐delay pseudo‐continuous arterial spin labeling: a simulation and in vivo study. (19th May 2020) - Ishida, Shota; Kimura, Hirohiko; Isozaki, Makoto; Takei, Naoyuki; Fujiwara, Yasuhiro; Kanamoto, Masayuki; Kosaka, Nobuyuki; Matsuda, Tsuyoshi; Kidoya, Eiji
Abstract : Arterial transit time (ATT) prolongation causes an error of cerebral blood flow (CBF) measurement during arterial spin labeling (ASL). To improve the accuracy of ATT and CBF in patients with prolonged ATT, we propose a robust ATT and CBF estimation method for clinical practice. The proposed method consists of a three‐delay Hadamard‐encoded pseudo‐continuous ASL (H‐pCASL) with an additional‐encoding and single‐delay with long‐labeled long‐delay (1dLLLD) acquisition. The additional‐encoding allows for the reconstruction of a single‐delay image with long‐labeled short‐delay (1dLLSD) in addition to the normal Hadamard sub‐bolus images. Five different images (normal Hadamard 3 delay, 1dLLSD, 1dLLLD) were reconstructed to calculate ATT and CBF. A Monte Carlo simulation and an in vivo study were performed to access the accuracy of the proposed method in comparison to normal 7‐delay (7d) H‐pCASL with equally divided sub‐bolus labeling duration (LD). The simulation showed that the accuracy of CBF is strongly affected by ATT. It was also demonstrated that underestimation of ATT and CBF by 7d H‐pCASL was higher with longer ATT than with the proposed method. Consistent with the simulation, the 7d H‐pCASL significantly underestimated the ATT compared to that of the proposed method. This underestimation was evident in the distal anterior cerebral artery (ACA; P = 0.0394) and the distal posterior cerebral artery (PCA; 2 P = 0.0255). Similar to the ATT, the CBF was underestimated with 7d H‐pCASL in the distal ACA (P = 0.0099), distal middle cerebral artery (P = 0.0109), and distal PCA (P = 0.0319) compared to the proposed method. Improving the SNR of each delay image (even though the number of delays is small) is crucial for ATT estimation. This is opposed to acquiring many delays with short LD. The proposed method confers accurate ATT and CBF estimation within a practical acquisition time in a clinical setting. Abstract : We proposed a robust ASL design, which consists of a theree delay Hadamard‐encoded pCASL (H‐pCASL) and long‐labeled long‐delay acquisition, to improve the accuracy of arterial transit time (ATT) and cerebral blood flow (CBF) measurement. The proposed method was compared to the original 7 delay H‐pCASL using the Monte Carlo simulation and in vivo experiment. The simulation and in vivo experiment demonstrated that 7d H‐pCASL significantly underestimated the ATT and CBF compared to the proposed method.